Twenty-year follow-up of a familial case of PTH1R-associated primary failure of tooth eruption - Kanno, Cláudia Misue [UNESP]; Oliveira, Jose Americo de [UNESP]; Garcia, Jose Fernando [UNESP]; Roth, Helmut; Weber, Bernhard H. F. (Elsevier B.V., 2017)
Introduction: Nonsyndromic primary failure of eruption (PFE) is a rare autosomal dominant disorder of dental eruption with no obvious dental or soft tissue interference. The purposes of this study were to genetically and clinically characterize a family with many members affected by PFE and to describe the natural evolution of the disorder. Methods: Three generations of a family with 18 members, 10 of them clinically affected by PFE, were evaluated periodically during 20 years of clinical follow-up. PFE was observed in varying degrees of severity in both sexes. Clinical presentation became more severe in adulthood. One patient had spontaneous reeruption of 2 posterior teeth. Cervical root resorptions were observed in 3 members. Genetic analysis showed a deleterious heterozygous mutation in intron 9 of the PTH1R gene (c.639-2A>G) and diagnosed an additional affected member. Conclusions: The long-term follow-up of PFE cases in this family permitted the following observations: (1) the onset occurred from the preemergence to the postemergence phases, (2) PFE appeared to be closely related to ankylosis, (3) affected teeth maintained the eruptive potential even in adulthood, (4) the earlier the onset the more severe the open bite, and (5) cervical root resorptions occurred in 3 affected members.